ANALISIS BIBLIOMETRIK: TREN RISET EPISTEMOLOGICAL OBSTACLE DARI TAHUN 2000–2022 - Ikbal Pauji; Rahmat Kusharyadi; Ahmad Zulfa Khotimi (IKIP Siliwangi, 2023)
Mathematics is an abstract science so that in the learning process it is often difficult for students to understand the material because students have learning difficulties. Learning barriers consist of 3 namely ontogenic obstacles, epistemological obstacles and didactical obstacles. This study aims to analyze the trend of writing articles with the theme of epistemological obstacles in mathematics learning from 2000 to 2022. Articles are analyzed based on country of origin, authors and institutions that produce articles with the most citations and link strength. The analysis uses the method of bibliometric analysis. The sample used was 61 search results articles using database dimensions with the keyword epistemological obstacles in mathematics. The results of the analysis show that this study fluctuates every year. Didi Suryadi is the author with the most authors and the author with the most total links and Athanasios Gagatsis is the author with the highest number of citations. The themes regarding form, learning obstacles, researchers, operations, participants, and didactical design research are the newest themes related to epistemological obstacles in mathematics so that they can become references for updating further research.